First record of the Lessepsian Sammara Squirrelfish, Neoniphon sammara (Forsskål, 1775), in the Egyptian Mediterranean waters - MEHANNA, SAHAR F.; OSMAN, YASSEIN A.A. (Mediterranean Marine Science, 2022)
This paper discusses the first record of the sammara squirrelfish, Neoniphon sammara in the Egyptian Mediterranean waters. On April 2020, 17 specimens of this species were recorded in the miscellaneous catch at the Mersa Matruh landing site on the Mediterranean Sea (31.33333° Ν, 27.216665° E), Egypt. The collected specimens represent the first record of N. sammara in the Egyptian Mediterranean waters. These specimens have a total length of 15.3 to 21.5 cm, fork length of 13.3 to 18.7 cm, standard length of 12.4 to 17.2 cm, and total weight of 45.3 to 125.1 g. The specimens’ morphometric measurements and meristic counts are described. These new findings increase the number of Lessepsian species from the Egyptian Mediterranean waters to 44 species.